Reanalysis of clause boundaries in Japanese as a constraint-driven process. - Miyamoto ET (Language & Speech, 2003)
When processing the initial segment of a sentence, readers may favor an interpretation that will turn out to be incorrect as more words are read. In these cases, a reanalysis process is necessary in order to correct the mental representation built up to that point. It has been previously proposed that readers obey a minimum change restriction, as they prefer to change the mental representation as little as possible. The present paper reports two experiments in Japanese suggesting that a minimal change restriction is unnecessary to characterize reanalysis. It is proposed instead that the present data and previous observations are more naturally explained by a constraint-driven model in which revisions are performed only when required by parsing constraints.